Conflict free trajectories development for air traffic assignment - Zafruddin Abdul Aziz, 1993- 611700 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2017